Indústria cultural e a Sociedade do espetáculo: esclarecimento reificado e subjetividade automática - Oliveira Júnior, Mário de Sena (2019)
The proposed theme in this research looks over to find out and to set up a conceptual connection among Theodor Adorno’s critical theory and Max Horkheimer’s, current in Enlightment Dialetic and Guy Debord’s critical theory from The Society of the Spectacle. These theoretical reflections were influenced by Marx’s work, A Contribution to the Critique of Political Economy, setted out by the very “Modernity” concept, which would be the commodity-based Western-capitalist civilization based on market economy, on exchange value, on private property, on awareness reification and on reality, in instrumental rationality and in life quantification. Firstly we will explain the Cultural Industry Critical theory joined by the contemporary world spectacular sociability, which includes the human being social relations between each other and nature itself. Entwined to this reflections we will analyse the benjaminian’s aproaches about capitalism as a religion. In another moment, we will expand the cultural industry and the spectacle concepts in the twenty-first century, reflectively reinterprating the key ideas of these authors in the new global scenery, entrenched on life virtualization through internet, where people build up a social experience on virtuality. Empiricism virtualization is a social device of control and dominance upon personal reified existence, submitting them to characteristically origins of spectacular images. With that, life seems to a real feebleness and nothingness in the presence of spectacular industry, deprived of a authentical historical meaning, in which language itself is reified. We consider here, nor the technology itself or its real potentiality to a new way of redeemer praxis, but the structuraly alienated and authoritarism objectively content of capitalist mass culture and the way in which new technologies reiterates theses controlled relations, which block critical thinking. It is the method and its technology anatomy that concur to capitalist social relations adjuration of individual inner nature domination and outward world’s nature.